Positive Health Externalities of Mandating Paid Sick Leave - Stefan Pichler; Katherine Wen; Nicolas R. Ziebarth (Institute of Labor Economics (IZA), 2020)
A growing economic literature studies the optimal design of social insurance systems and the empirical identification of welfare-relevant externalities. In this paper, we test whether mandating employee access to paid sick leave has reduced influenza-like-illness (ILI) transmission rates as well as pneumonia and influenza (P&I) mortality rates in the United States. Using uniquely compiled data from administrative sources at the state-week level from 2010 to 2018 along with difference-in-differences methods, we present quasi-experimental evidence that sick pay mandates have causally reduced doctor-certified ILI rates at the population level. On average, ILI rates fell by about 11 percent or 290 ILI cases per 100,000 patients per week in the first year.
Keywords: H23; H75; I12; I14; I18; J22; J38; J58; 330; sick pay mandates; population health; flu infection; negative externalities